Hubungan tingkat kepositifan BTA dengan LED pada pasien TB - Santi Indra Noviana (FKU 15 UMY 561, 2015)
*561 Background: Tuberculosis (TB) is one of the world's attention infectious disease today. Program Directly Observed Treatment Shortcourse (DOTS) has been recommended by WHO as a strategy for detection and cure of TB patients, especially for new sputum smear-positive pulmonary TB case. Acid Fast Bacillus positivity level can act as a marker of the infectious degree whereas the hematological changes can act as a marker for the diagnosis, prognosis and response to therapy of TB disease. ESR is the one of the most common hematologic changes found in TB and it can become one of the signs of chronic disease. This study is required to know the relation of AFB sputum-smear positivity levels with decreased levels of ESR in TB patients. Methods: The research was performed by using observational analytic design with cross sectional approach. The sample of this research were 38 TB patients aged 15-50 years old who has been done sputum examination and complete blood count at RS PKU Muhammadiyah Yogyakarta Unit 1. This study data analysis using Spearman correlation test method. Result: The prevalence TB in men was higher than women (74% : 26%). TB patients with AFB 1+ is 10 people (26%), AFB +2 is 13 people (34%) and the AFB +3 is 15 people (40%). The Spearman analysis result show that there is significantly relations between AFB positivity level and ESR level (p<0,05). TB patients with +1 AFB who has high ESR levels is 3 people while has normal ESR levels is 7 people. TB patients with 2+ AFB who has high ESR levels is 7 people while has normal ESR levels is 6 person. TB Patients with 3+ AFB who has high ESR levels is 10 people and has normal ESR levels is 5 people. Nobody have decrease levels of ESR for all TB patients with 1+, 2+ and 3+ AFB sputum-smear. Conclusions : TB patients with positive AFB sputum-smear mostly has increase ESR. AFB sputum-smear positivity rate is associated with increase levels of ESR in TB patients. Keywords: AFB sputum-smear positivity levels examination, ESR, tuberculosis.